Coefficient Inequalities for a Novel Class of m-Fold Symmetric Bi-Univalent Functions Related to λ-Pseudo-Starlike and λ-Pseudo-Convex Functions - Shahad Kareem Atiyah; Abbas Kareem Wanas; Fethiye Muge Sakar (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2026)
This article addresses the problem of coefficient bounds for certain subclasses of normalized holomorphic and m-fold symmetric bi-univalent functions associated with λ-pseudo-starlike and λ-pseudo-convex structures in the open unit disk Ữ. Upper estimates for the initial Taylor–Maclaurin coefficients are derived for two newly considered families. Several previously known results follow as particular instances of the obtained estimates.